Corporate governance and technical efficiency of government linked companies (GLCs) in Malaysia: a stochastic frontier approach / Jennifer Tunga Janang - Tunga Janang, Jennifer (Institute of Graduate Studies, UiTM, 2018)
The performance of government linked companies (GLCs) has been the subject of scrutiny from both the perspective of academic research and policy formulation. With trade liberalization and increasing global market competition, GLCs efficiency becomes relevant to ensure sustainable economic growth not only for the Malaysian economy but to remain as key players in the regional and international markets. Corporate governance and how it has affected firm performance is a much-debated issue and there is voluminous literature aimed at understanding its role in maximizing firm profitability and market value. However, studies on its effects on the economic efficiency as another indicator for performance are still minimal. This study’s objectives are two folds: First, applying the Stochastic Frontier analysis with inefficiency effects model, in estimating technical efficiency of GLCs against selected foreign owned firms (FFs) as international benchmark. The analysis uses 31 GLCs and 15 FFs listed in Bursa Malaysia over a period between 2001 and 2012 (12 years). Second, applying a similar model to the 31 GLCs over the same period, and allowing inefficiency effects to be a function of a set of explanatory variables, that measures corporate governance mechanism…